Creating Markets in Madagascar : For Inclusive Growth - Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
The report is organized as follows: the first part gives an overview of recent economic and private sector trends, followed by an in-depth review of the cross-cutting constraints that affect private sector participation. The CPSD recommends putting a special focus on resolving three types of constraints: (a) deep-rooted governance issues (especially as they relate to policy unpredictability, red tape, and the uneven playing field in key sectors of the economy); (b) infrastructure bottlenecks, focusing on transport connectivity and energy; and (c) limited and poorly functioning factor markets for human capital, access to finance, and land. The second part lays out opportunities and policy options to strengthen competitiveness in agribusiness, apparel, and tourism. The three sectors reviewed are deemed to hold a high potential for job creation and growth and have been prioritized by the PEM and by the private sector stakeholders and development partners consulted for the report. The review puts a lens on addressing gender gaps, policies to promote sustainability, and opportunities to increase the impact of information and communication technology (ICT) as an enabler for development, where relevant.